Development of A Website-Based Project Management Information System - Suharno, FA Suharno; Imraan , Mohd (The International Journal of Education Management and Sociology, 2024)
This research aims to find out if this project management information system uses the most commonly used waterfall model. Creating web-based application programming using HTML and PHP with MySQL used as the database server. The research method uses a qualitative approach through observation, interviews, and literacy studies. Conclusion In the information system, each work progress is updated every week via a Dashboard page input by the service provider, in an integrated manner and an online project document archiving system that can be accessed at any time by the relevant parties. The history of activities, both problems and solutions during project implementation, is recorded on this Website through the Discussion and Photo sections so that it can be used as a reference for planning and implementing similar projects in the future. Data and information as well as documents stored on the server make storage easier and faster as well as functioning as backup documents for physical/hardcopy documents in digital form. Apart from understanding project implementation, responses and input from potential users are very helpful in developing the Website. It is necessary to improve existing features and add new features according to the needs of the project owner so that this website-based project management information system can function optimally